Pengaruh Pelatihan Terhadap Kinerja Karyawan Pada Departemen Customer Service Indonesia di BPO Port City-Sri Lanka - Yuliani, Glenny Byanca (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the impact of employee training on the performance of staff in the Indonesian Customer Service Department at BPO Port City, Sri Lanka. In the Business Process Outsourcing (BPO) industry, the quality of customer service is heavily reliant on employee competence and professionalism. BPO Port City, as a leading customer service provider, faces challenges in ensuring its employees possess the necessary skills to meet customer expectations. This research is grounded in the importance of training in enhancing employee skills and knowledge, ultimately aiming to improve employee performance. The problem addressed in this study is whether the training provided significantly influences the performance of employees in the Indonesian Customer Service Department at BPO Port City. The research employs a quantitative approach with a survey technique. Data will be collected through questionnaires distributed to 20 employees in the Indonesian Customer Service Department at BPO Port City, Sri Lanka. Data analysis will utilize descriptive statistics and simple linear regression to examine the relationship between training and employee performance using SPSS software. Preliminary findings indicate that training positively and significantly affects employee performance. Proper training can enhance employees’ abilities to complete their tasks more efficiently, thereby contributing to improved performance. These findings recommend that BPO Port City’s management continue to enhance training programs to support organizational goals.